Simple and Rapid Enzymatic Method for the Synthesis of Single-Strand Oligonucleotides Containing Trifluorothymidine - Suzuki, Norihiko (Taylor & Francis, 2010)
To investigate the mechanism of trifluorothymidine (TFT)-induced DNA damage, we developed an enzymatic method for the synthesis of single-strand oligonucleotides containing TFT-monophosphate residues. Sixteen-mer oligonucleotides and 14-mer 5′-phosphorylated oligonucleotides were annealed to the template of 25-mer, so as to empty one nucleotide site. TFT-triphosphate was incorporated into the site by DNA polymerase and then ligated to 5′-phosphorylated oligonucleotides by DNA ligase. The synthesized 31-mer oligonucleotides containing TFT residues were isolated from the 25-mer complementary template by denaturing polyacrylamide electrophoresis. Using these single-strand oligonucleotides containing TFT residues, the cleavage of TFT residues from DNA, using mismatch uracil-DNA glycosylase (MUG) of E.coli origin, was compared with that of 5-fluorouracil (5FU) and 5-bromodeoxyuridine (BrdU). The TFT/A pair was not cleaved by MUG, while the other pairs, namely, 5FU/A, 5FU/G, BrdU/A, BrdU/G, and TFT/G, were easily cleaved from each synthesized DNA. Thus, this method is useful for obtaining some site-specifically modified oligonucleotides.